A low-power D flip flop integrated by metal oxide thin film transistors employing internal feedback control. (4th October 2018) - Zhan, Fan; Wu, Jian-Dong; Zhou, Lei; Zou, Jian-Hua; Tao, Hong; Xu, Miao; Wang, Lei; Huang, Mo; Liu, Yu-Rong; Wu, Wei-Jing; Peng, Jun-Biao
Abstract: The conventional D flip flop (DFF) consists of six pseudo-CMOS NOR gates integrated by monotype transistors. By analyzing the six logic states of the conventional DFF, it is found that the three-input NOR gate can be replaced by a new three-input NOR gate with a pull-up control signal and the pull-up control signal is connected to an output of another NOR gate. As a result, a new DFF is developed by using such an internal feedback control method. The static power consumption can be reduced by cutting off the dc path properly in the proposed DFF. For comparison, the conventional DFF and the proposed DFF are both fabricated by metal oxide thin film transistors with an etch stop layer structure on the basis of the same design parameters. Both the conventional DFF and the proposed DFF have the same function and both work using the negative edge triggered method. The measured power consumption of the proposed DFF is at least 13% less than that of the conventional DFF under the condition of a 20 kHz clock signal.